Are vacilins another major class of legume lectins ? - Ribeiro, Ana C. (2017)
Legume lectins comprise a structurally related, Ca/Mn-dependent, widespread, abundant and well characterized lectin family when compared to the large number of lectins from other sources described in the literature. Strangely enough, no specific function has been assigned to them aside from a possible role in storage and/or defense. Using a recent and fine-tuned methodology capable of specific lectin identification, β-conglutin, Vicia faba vicilin and β-lathyrin, the vicilin storage globulins from Lupinus albus, V. faba and Lathyrus sativus, respectively, were shown to be capable of affinity binding to thoroughly washed erythrocyte membranes and of specific elution with appropriate sugars. Based on this evidence and on sparse data published in the literature, a second family of legume lectins is proposed: the 7S family of storage proteins from leguminous seeds, or family II of legume lectins. These lectins are also structurally related, widespread and well characterized. In addition, they self-aggregate in a Ca/Mg, electrostatic dependent manner and are even more abundant than the family I of legume lectins. Using the same evidence, reserve and defense roles may be attributed to family II of legume lectins